2019
DOI: 10.1186/s13634-019-0631-7
|View full text |Cite
|
Sign up to set email alerts
|

Stationary time-vertex signal processing

Abstract: The goal of this paper is to improve learning for multivariate processes whose structure is dependent on some known graph topology; especially when the number of available samples is much smaller than the number of variables. Typically, the graph information is incorporated into the learning process via a smoothness assumption postulating that the values supported on well-connected vertices exhibit small variations. We argue that smoothness is not enough. To capture the behavior of complex interconnected syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 60 publications
0
42
0
Order By: Relevance
“…In analogy with the definition of the JFT, stationarity can be extended to time-varying graph processes [16]. This new concept of stationarity requires now that the first and second order moments are jointly preserved along the graph and temporal dimension.…”
Section: Stationarity On Networkmentioning
confidence: 99%
See 3 more Smart Citations
“…In analogy with the definition of the JFT, stationarity can be extended to time-varying graph processes [16]. This new concept of stationarity requires now that the first and second order moments are jointly preserved along the graph and temporal dimension.…”
Section: Stationarity On Networkmentioning
confidence: 99%
“…Continuing our prior works [16], [17], we exploit the (approximate) time-vertex stationarity of graph time series and extend classical VAR and vector autoregressive moving average (VARMA) recursions for modeling and predicting timevarying processes on graphs. Specifically, the contributions of this work are: 1) We propose VAR and VARMA models for forecasting time series on graphs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In [34], vector autoregressive (VAR) and vector autoregressive moving average (VARMA) models are proposed for predicting time-varying processes on graphs. Joint time-vertex stationarity is introduced for time-varying graph signals in [35], [36], and a joint time-vertex harmonic analysis for graph signals is proposed in [37]. It is shown that joint stationarity facilitates estimation or recovery tasks when compared to purely time or graph methods.…”
mentioning
confidence: 99%